Examining the leadership roles of women principals; their contributions to instructional and administrative development - Madriaga, Judy R. (San Miguel, Iriga City: University of Saint Anthony, 2018)
Examining the leadership roles of women principals; their contributions to instructional and administrative development.
Includes bibliographical references.
English
Keywords: leadership roles of women principals